Nitrous oxide: a unique official French addictovigilance national survey - Guerlais, Marylène; Aquizerate, Aurélie; Lionnet, Arthur; Daveluy, Amélie; Duval, Mélanie; Gérardin, Marie; Istvan, Marion; Laforgue, Edouard-Jules; Victorri-Vigneau, Caroline, for French Addictovigilance Network (Frontiers in Public Health, 2023)
Introduction: Nitrous oxide has become over the last few years a public health problem in many countries. France has a unique health monitoring system dedicated to the surveillance of the abuse, dependence and consequences associated with the use of psychoactive substances coordinated by the French National Agency for the Safety of Medicines and Health Products. We present the French national survey of nitrous oxide. Materials and methods: We analysed (i) all the cases with nitrous oxide from 2012 to 2021 and (ii) their evolutions over time. Results: 525 cases were received with an exponential increase since 2019 and a change in the characteristics of the notifications with (i) an increase in the proportion of women (42.7% in 2021 versus 30.8% in 2020 (p=0.02)); (ii) an increase in the quantities consumed (use of cylinders); (iii) a negative evolution of the contexts of use with a search for self-therapeutic effects and use in violent contexts. The main effects were substance use disorders and/or associated criteria (82.5%), neurological disorders (75.4%), psychiatric symptoms (15.4%) and cardiovascular events (8.6%). In terms of evolution, there is (i) an increasing trend of the severity of cases (78.1% in 2021 versus 70.0% in 2020 (p=0.07)) and (ii) the identification of new serious effects, notably cardiovascular events. Discussion: The combination of high availability, varied effects from euphoria to relief of discomfort in a stressful global pandemic context and the development of dependence could explain the rapid growth of consumption and the seriousness of the cases. It must now be taken into account that (i) nitrous oxide is an addictive substance; (ii) clinicians must consider "nitrous oxide" in young subjects presenting different types of manifestations; and (iii) stopping consumption is imperative and is the first treatment. In this context, an addictological assessment must also be carried out.